The association between lipid-related obesity indicators and severe headache or migraine: a nationwide cross sectional study from NHANES 1999 to 2004 - Xu Sun; Jimei Song; Rixun Yan; Jianwei Diao; Yibo Liu; Zhangzhi Zhu; Weichi Lu (Lipids in Health and Disease)
Abstract Background The connection between lipid-related obesity indices and severe headache or migraine in young and middle-aged people aged 20–60 remains ambiguous, and there are gaps in the discriminative ability of different indicators for severe headaches or migraines. Consequently, we set out to look into this association utilizing National Health and Nutrition Examination Survey (NHANES) data from 1999 to 2004. Methods After the values of waist-to-height ratio (WHtR), body-mass index (BMI), body roundness index (BRI), visceral adiposity index (VAI), lipid accumulation product (LAP), triglyceride glucose index (TyG), cardiac metabolism index (CMI), waist triglyceride Index (WTI), conicity index (CI) and weight-adjusted waist index (WWI) were estimated, with minimal sufficient adjustment for confounders determined by directed acyclic graph (DAG), weighted univariable and multivariable logistic regression analyses were carried out to ascertain the relationship between them and migraine. Stratified analysis and cross-effect analysis were implemented to examine the variability of intergroup correlations. Restricted cubic splines (RCS) and receiver operating characteristic (ROC) were then employed to examine nonliner relationships and its discriminatory ability for severe headache or migraine, respectively. Results 3354 United States adults were involved in our study, of whom 839 (25.01%) had severe headache or migraine. After adjusting for relevant covariables, WHtR, BRI, BMI, LAP, WTI and VAI were all associated with migraine and WHtR (OR = 6.38, 95% CI: 2.25,18.09, P < 0.01) showed the best predictive ability. Additionally, WHtR, BMI, and BRI demonstrated linear dose-response relationships with the prevalence of migraine (all P overall < 0.05, P non−linearity > 0.05). Conclusions Among those ten lipid-related obesity indicators evaluated in the study, WHtR, BMI and BRI demonstrated linear positive dose-response relationships with the prevalence of migraine in young and middle-aged individuals within the United States and WHtR showed the best predictive ability. Our study can provide important insight into epidemiological research and comprehensive management of obese patients with migraine.